Assisted reproductive technology outcomes and gene expression in unexplained infertility patients - Vaigauskaitė-Mažeikienė, Brigita; Baušytė, Raminta; Valatkaitė, Elvina; Maželytė, Rūta; Kazėnaitė, Edita; Ramašauskaitė, Diana; Navakauskienė, Rūta (Frontiers in Cell and Developmental Biology, 2023)
Background: Unexplained infertility (UI) can be a frustrating and challenging diagnosis for doctors and couples as it can be difficult to understand why they are unable to conceive despite increasing diagnostic tools. Assisted reproductive technology (ART) procedures have been successfully applied to many couples aiming to overcome UI. However, they can be not only expensive but also require multiple cycles to achieve a successful pregnancy. The endometrium and the follicular fluid have been investigated as target tissues not only to determine the cause of UI but also to increase conception rates. Results: In this study, we analyzed the outcomes of ART in 223 UI couples and gene expression associated with DNA modification, cell death, immune response and senescence (TET1, TET2, BCL2, BAK1, HMGA2, IL-6, IL-8) in infertile women’s endometrium and follicular fluid. We found significant differences in women who successfully got pregnant compared to women unable to conceive depending on age, duration of infertility, number of retrieved oocytes, zygotes, transferred embryos. Further, the expression of genes BAK1 (pro-apoptotic), TET2 (associated with epigenetic DNA modification) and IL-6 (associated with immune responses) were significantly higher in the endometrium of women who successfully got pregnant. Conclusion: Younger parental age couples showed higher ART success rates, shorter duration of infertility, higher number of retrieved oocytes, zygotes and transferred embryos. The gene expression analysis revealed significant changes in the endometrium depending on genes associated with cell death and immune response which were upregulated in females with diagnosed unexplained infertility.